ZVI (Fe0) Desalination: Stability of Product Water - David D. J. Antia (Resources, 2016)
A batch-operated ZVI (zero valent iron) desalination reactor will be able to partially desalinate water. This water can be stored in an impoundment, reservoir or tank, prior to use for irrigation. Commercial development of this technology requires assurance that the partially-desalinated product water will not resalinate, while it is in storage. This study has used direct ion analyses to confirm that the product water from a gas-pressured ZVI desalination reactor maintains a stable salinity in storage over a period of 1–2.5 years. Two-point-three-litre samples of the feed water (2–10.68 g (Na+ + Cl−)·L−1) and product water (0.1–5.02 g (Na+ + Cl−)·L−1) from 21 trials were placed in storage at ambient (non-isothermal) temperatures (which fluctuated between −10 and 25 °C), for a period of 1–2.5 years. The ion concentrations (Na+ and Cl−) of the stored feed water and product water were then reanalysed. The ion analyses of the stored water samples demonstrated: (i) that the product water salinity (Na+ and Cl−) remains unchanged in storage; and (ii) the Na:Cl molar ratios can be lower in the product water than the feed water. The significance of the results is discussed in terms of the various potential desalination routes. These trial data are supplemented with the results from 122 trials to demonstrate that: (i) reactivity does not decline with successive batches; (ii) the process is catalytic; and (iii) the process involves a number of steps.